FAKTOR YANG MEMPENGARUHI MINAT BACA WARGA BELAJAR PAKET C PADA TAMAN BACAAN DI SPNF SKB JALAN KHATIB SUTAN NO.3 KELURAHAN CINTA RAJA KECAMATAN SAIL - Asmi, Nur; Jas, Jaspar; Widiastuti, Widiastuti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study aims to determine the dominant factors that influence the reading interest of the studying citizens of package C at the reading park at SPNF SKB Jalan Khatib Sutan No. 3 Kelurahan Cinta Raja Kecamatan Sail. The formulation of the problem of this research is where the dominant factor that influences the interest of reading citizens learning package C at the park reading in SPNF SKB Jalan Khatib Sutan No.3 Kelurahan Cinta Raja Kecamatan Sail. The population in this study as many as 38 people. So this study uses a saturated sample so that all the population sampled that is as many as 38 people, and 20 people to sample trials in PKBM Pucuk Rebung Pekanbaru. The type of this research is descriptive with quantitative approach. Instrument data collection is a questionnaire with 40 statements and after the test remaining 35 valid statements to be used as research instruments. Data analysis through quantitative descriptive analysis. The findings of this study indicate that the factors that influence the reading interest of citizens learning package C at the park reading in SPNF SKB Jalan Khatib Sutan No.. 3 Kelurahan Cinta Raja Kecamatan Sail is dominant with internal factor with percentage 43,3%.Keywords: Reading Interest. Residents of Learning, Community Reading Garden